PENGARUH DISIPLIN, PENGAWASAN, DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI DI PERUM BULOG KANWIL JAWA TIMUR (Agridevina : Berkala Ilmiah Agribisnis, 2022)
BULOG is a state-owned public company that is important in the distribution of food logistics. The success of a company in achieving its goals is certainly influenced by many factors, one of which is the productivity of human resources. In improving the productivity of human resources, it is necessary to improve the quality and effectiveness of work that is influenced by good work discipline, work supervision and a supportive environment. The purpose of this study is to identify the procedures and implementation of disciplinary regulations, supervision and work environment and its influence on the effectiveness of employee work in the Bulog Regional Office of East Java. This research was conducted at Bulog Regional Office of East Java. This study uses an associative approach with primary data sources. Data collection techniques are through interviews, observations and questionnaires. Sampling techniques used are purposive sampling and obtained by 34 respondents. The result of this research is the procedure on the discipline, supervision and work environment presented by the company has been agreed by all employees and has a rule book for each employee. The application of discipline, supervision and work environment regulations has been established by the company, all employees have complied with the regulations well. The work environment affects the effectiveness of work, but discipline and supervision of work have no effect on the effectiveness of employee work in the Bulog Regional Office of East Java.  DOI : https://doi.org/10.33005/adv.v11i1.3092